2020
DOI: 10.1007/s11606-020-05782-6
|View full text |Cite|
|
Sign up to set email alerts
|

Excess Weight Gain After Cure of Hepatitis C Infection with Direct-Acting Antivirals

Abstract: BACKGROUND: Cure from chronic hepatitis C virus (HCV) infection is readily achievable with direct-acting antivirals (DAA), but little is known about optimal management after treatment. Weight gained after DAA treatment may mitigate benefits or increase risk for liver disease progression. As the single largest sample of HCVinfected individuals receiving DAA treatment in the United States, the Veterans Affairs (VA) Birth Cohort is an ideal setting to assess weight gain after DAA treatment. METHODS: We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 53 publications
2
24
2
1
Order By: Relevance
“…As an independent predictor for a further decline in MCS after DAA therapy, a BMI of >30 kg/m 2 was evaluated for patients with low BL values. This finding might be in line with results of previously performed studies, showing weight gain in up to 52% of patients treated with DAA, even among those who are overweight at treatment BL 47,48 . The prevalence of steatosis and steatohepatitis in obese patients was determined before by histological findings in a minimum of 65% and 20%, respectively (notably influenced by ethical background and genetic variation) 49 and NAFLD was reported as an independent predictor of poorer HRQoL compared to HCV‐infected patients, 50 associated with hepatic inflammation levels 51 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As an independent predictor for a further decline in MCS after DAA therapy, a BMI of >30 kg/m 2 was evaluated for patients with low BL values. This finding might be in line with results of previously performed studies, showing weight gain in up to 52% of patients treated with DAA, even among those who are overweight at treatment BL 47,48 . The prevalence of steatosis and steatohepatitis in obese patients was determined before by histological findings in a minimum of 65% and 20%, respectively (notably influenced by ethical background and genetic variation) 49 and NAFLD was reported as an independent predictor of poorer HRQoL compared to HCV‐infected patients, 50 associated with hepatic inflammation levels 51 .…”
Section: Discussionsupporting
confidence: 86%
“…This finding might be in line with results of previously performed studies, showing weight gain in up to 52% of patients treated with DAA, even among those who are overweight at treatment BL. 47,48 The prevalence of steatosis and steatohepatitis in obese patients was determined before by histological findings in a minimum of 65% and 20%, respectively (notably influenced by ethical background and genetic variation) 49 and NAFLD was reported as an independent predictor of poorer HRQoL compared to HCV-infected patients, 50 associated with hepatic inflammation levels. 51 The absence of improvement or even further decline in MCS therefore may be associated with a coincidently existent NAFLD component in obese HCV-infected patients.…”
Section: Endpointmentioning
confidence: 99%
“…This increase was deemed of interest considering an expected weight gain associated with aging (0.45 to 0.9 kg per year). 33 SVR was an independent predictor of weight gain together…”
Section: Recognising the Impact Of Comorbiditiesmentioning
confidence: 92%
“…A large American study of 11,469 DAAs‐treated patients showed that while 78% of patients were already overweight or obese at DAA treatment initiation, 53% of patients gained weight and 20% gained excess weight (defined as weight change ≥10 lbs over the 2‐year observation period) after 2 years of follow‐up. Achieving SVR was an independent predictor of weight gain 50 . There is also strong evidence showing an increase in total cholesterol and low‐density lipoprotein (LDL) levels after HCV eradication with DAA 48,49,51,52 .…”
Section: Are Svr Populations Vulnerable To Mafld‐negative Impact?mentioning
confidence: 99%
“…Achieving SVR was an independent predictor of weight gain. 50 There is also strong evidence showing an increase in total cholesterol and low-density lipoprotein (LDL) levels after HCV eradication with DAA. 48,49,51,52 Another study also confirmed the significant increase in low-density lipoprotein and total cholesterol, regardless of the degree of hepatic fibrosis, while no significant change in lipid profile was noticed in both untreated and non-SVR patients.…”
Section: Are S Vr P Opul Ati On S V Ulner Ab Le To Mafld -Neg Ativementioning
confidence: 99%